Scale up fermentation of Chenopodium formosanum dairy products with process optimization and evaluation of ACE inhibitory peptides and antioxidant activity - Chen-Che Hsieh; Jing-Rong Wu; Yi-Cheng Huang; Shin-Ping Lin; Jheng-Jhe Lu; Adyasa Barik; Shella Permatasari Santoso; Chang-Wei Hsieh; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2026)

Ganoderma formosanum— advances in biotechnological fermentation, bioactive metabolites, and health-promoting applications: a critical review (2017–2025) - Kitipong Assatarakul; Khanom Simarani; Chen-Che Hsieh; Shin-Ping Lin; Isaya Kijpatanasilp; Yueh-Hao Ronny Hung; Saeid Jafari; Kuan-Chen Cheng (Critical Reviews in Food Science and Nutrition, 2026)

Process-intensified synthesis of sulfonated peanut shell char through dilute acid hydrolysis and low-temperature sulfonation–carbonization for Pb2 + removal - Maria Stefani; Kuan-Chen Cheng; Theresia Angeline Veronica; Shella Permatasari Santoso; Edward Hartman Ernest; Shin-Ping Lin; Jindrayani Nyoo Putro; Wiyanti Fransisca Simanullang; Hsien-Yi Hsu; Chang-Wei Hsieh; Suryadi Ismadji (Journal of Environmental Chemical Engineering, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Aqueous LC-MS/MS quantification of α-/β-nicotinamide mononucleotide in dietary supplements using a pentabromophenyl column - Chng Sze Hoei; Nian-Hua Wu; Chao-Ming Tsen; Ping-Wei Sun; Han-Wei Chang; Shin-Yuan Wang; Hung-Yu Lin (Analytica Chimica Acta, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Antimicrobial efficacy of carvacrol-loaded curdlan hydrogels for enhancing shelf-life in seafood packaging applications - Hong-Ting Victor Lin; Yi-Chi Yu; Shu-Han Yu; Yu-Chieh Chou; Hsuan-Ju Lin; Shella Permatasari Santoso; Shin-Ping Lin (International Journal of Food Microbiology, 2025)

Enhancing miso production with optimized puffed-rice koji and its biological function evaluation - Shin-Ping Lin; Yu-Chieh Chou; Chiao-En Chen; Yen-Tso Lai; Chen-Che Hsieh; Tsung-Yu Tsai; Yun-Hsin Lin; Shella Permatasari Santoso; Hui-Wen Lin; Kuan-Chen Cheng (Food Bioscience, 2024)

Agar-altered foaming bacterial cellulose with carvacrol for active food packaging applications - Anita Chandra Kusuma; Yu-Chieh Chou; Chen-Che Hsieh; Shella Permatasari Santoso; Alchris Woo Go; Hong-Ting Victor Lin; I.-Lun Hsiao; Shin-Ping Lin (Food Packaging and Shelf Life, 2024)

Modification of cellulosic adsorbent via iron-based metal phenolic networks coating for efficient removal of chromium ion - Valentino Bervia Lunardi; Kuan-Chen Cheng; Shin-Ping Lin; Artik Elisa Angkawijaya; Alchris Woo Go; Felycia Edi Soetaredjo; Suryadi Ismadji; Hsien-Yi Hsu; Chang-Wei Hsieh; Shella Permatasari Santoso (Journal of Hazardous Materials, 2024)

An innovative targeted therapy for fluoroscopy-induced chronic radiation dermatitis - Kai-Che Wei; Shih-Fan Lai; Wei-Lun Huang; Kuo-Chung Yang; Ping-Chin Lai; Wan-Ju Wei; Tsung-Hsien Chang; Yun-Chen Huang; Ya-Chuan Tsai; Shin-Chih Lin; Sun-Jang Lin; Shih-Chieh Lin (Journal of Molecular Medicine, 2022)
Fluoroscopy-induced chronic radiation dermatitis (FICRD) is a complication of fluoroscopy-guided intervention. Unlike acute radiation dermatitis, FICRD is different as delayed onset and usually appears without preexisting acute dermatitis. Unfortunately, the chronic and progressive pathology of FICRD makes it difficult to treat, and some patients need to receive wide excision and reconstruction surgery. Due to lack of standard treatment, investigating underlying mechanism is needed in order to develop an effective therapy. Herein, the Hippo pathway is specifically identified using an RNA-seq analysis in mild damaged skin specimens of patients with FICRD. Furthermore, specific increase of the Yes-associated protein (YAP1), an effector of the Hippo pathway, in skin region with mild damage plays a protective role for keratinocytes via positively regulating the numerous downstream genes involved in different biological processes. Interestingly, irradiated-keratinocytes inhibit activation of fibroblasts under TGF-β1 treatment via remote control by an exosome containing YAP1. More importantly, targeting one of YAP1 downstream genes, nuclear receptor subfamily 3 group C member 1 (NR3C1), which encodes glucocorticoid receptor, has revealed its therapeutic potential to treat FICRD by inhibiting fibroblasts activation in vitro and preventing formation of radiation ulcers in a mouse model and in patients with FICRD. Taken together, this translational research demonstrates the critical role of YAP1 in FICRD and identification of a feasible, effective therapy for patients with FICRD. Key messages • YAP1 overexpression in skin specimens of radiation dermatitis from FICRD patient. • Radiation-induced YAP1 expression plays protective roles by promoting DNA damage repair and inhibiting fibrosis via remote control of exosomal YAP1. • YAP1 positively regulates NR3C1 which encodes glucocorticoid receptor expression. • Targeting glucocorticoid receptor by prednisolone has therapeutic potential for FICRD patient.

Developing a reliable model for aquifer vulnerability - Cheng-Shin Jang; Chien-Wen Lin; Ching-Ping Liang; Jui-Sheng Chen (Stochastic Environmental Research and Risk Assessment, 2016)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

Spatiotemporal distribution of arsineic species of oysters (Crassostrea gigas) in the coastal area of southwestern Taiwan - Chen-Wuing Liu; Yung-Kay Huang; Yu-Mei Hsueh; Kao-Hung Lin; Cheng-Shin Jang; Lan-Ping Huang (Environmental Monitoring and Assessment, 2008)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Azo dye decolorization with a mutant Escherichia coli strain - Jo-Shu Chang; Tai-Shin Kuo; Yun-Peng Chao; Jin-Yen Ho; Ping-Jei Lin (Biotechnology Letters, 2000)